2015
DOI: 10.5937/zasmat1503335s
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of peroxidase from fresh horseradish extract for anthraquinone dye decolorization

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This was an indication that the immobilized peroxidase was more stable under alkaline conditions (Darwish et al, 2019). Sekuljica et al (2015), obtained 94.7% color removal efficiency at pH 4 and a reaction time of 15 min using horseradish peroxidase enzyme. Han F. et al (2020) observed in their activities that the pepsin enzyme had max.…”
Section: Effect Of Ph On Cod and Color Removalmentioning
confidence: 97%
“…This was an indication that the immobilized peroxidase was more stable under alkaline conditions (Darwish et al, 2019). Sekuljica et al (2015), obtained 94.7% color removal efficiency at pH 4 and a reaction time of 15 min using horseradish peroxidase enzyme. Han F. et al (2020) observed in their activities that the pepsin enzyme had max.…”
Section: Effect Of Ph On Cod and Color Removalmentioning
confidence: 97%
“…After that, the sample was centrifuged (at 10,000 rpm for 10 min), and the absorbance was measured. Equation 5 was used to compute the % decolorization [21].…”
Section: Decolorization Of Dyes With Citrus Lemon Peroxidase (Clp)mentioning
confidence: 99%
“…Similar experiments were conducted to optimize temperature (25 °C-95 °C), enzyme dose (0.05-0.2), and H 2 O 2 concentration (0.05-0.2 mM). The incubation time (5-60 min) was calculated [21]. All the studies were carried out in test tubes with a shaking water bath.…”
Section: Optimization Of Peroxidase Activity For Dye Decolorizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained enzyme-clay complex was used for the treatment of wastewater polluted with phenol. Fumed silica served as the support for the adsorp-tion of HRP and immobilized biocatalyst was successfully applied in the AV 109 dye removal [16].…”
Section: Introductionmentioning
confidence: 99%